An Unusual Manifestation of Q Fever: Peritonitis - Gülden Yılmaz; Bengi Öztürk; Osman Memikoğlu; Belgin Coşkun; Aysun Yalçı; Özge Metin; Hatice Ünal; Halil Kurt (Elsevier, 2015)
Summary: Q fever has rarely been reported and can be difficult to diagnose, especially in immunocompromised patients. In the present report, we describe an unusual case of Q fever that presented as peritonitis and was treated with long-term combination therapy with doxycycline, ciprofloxacin and rifampicin for five weeks in a patient who had been on peritoneal dialysis for six years due to hypertensive nephropathy. Keywords: Q fever, Coxiella burnetii, Peritonitis